BIOLOGY AND IN-VITRO GERMINATION BEHAVIOUR OF CITRULLUS COLOCYNTHIS (TUMBA) SEEDS AFTER PRETREATMENTS - SAHOO , KSHAN PRABHA; K. KASERA, PAWAN (The Bioscan, 2013)
Citrullus colocynthis is an important medicinal plant of the Indian Thar desert known as food of scarcity. The present paper deals with seed biology and germination behaviour under controlled laboratory (in-vitro) conditions. Results revealed that one-year-old seeds exhibited 86.67% viability as compared to fresh ones (43.33%), which indicates that seeds require resting period for maturity. Fresh and one-year-old stored seeds showed 6.67 and 66.67% germination, respectively under in-vitro conditions. The germination percentage can be enhanced significantly when seeds were pretreated with 2 minutes of concentrated H2SO4 and presoaked in 25 and 50mg L-1 concentrations of NH4NO3 for 24 and 48h, respectively.